Unified Field Theory - Poudel, Parashu Ram (Himalayan Physics, 2013)
Unified field theory is the long-sought means of tying together all known phenomena to explain the nature and behaviour of all matter and energy in existence. The quest for unification has been the perennial theme of modern physics. The belief that all physical phenomena can be reduced to simple and explained by a smaller number of laws is the central tenet of physics. Such a theory could potentially unlock all the secrets of nature and make a myriad of wonders possible, including such benefits as time travel and an inexhaustible source of clean energy, among many others. This paper aims to explain unified theory and its development towards the unification of four interactions in brief. The Himalayan Physics Vol. 4, No. 4, 2013 Page:87-90 Uploaded date: 12/23/2013